Pojęcie kryzysu w filozofii i naukach społecznych a kryzysy prawne - Skuczyński, Paweł (Filozofia Publiczna i Edukacja Demokratyczna, 2018)
The aim of this article is to discuss different approaches to the phenomena of crisis, which are reconstructed from chosen philosophical and social sciences theories. Latest popularity of the notion of legal or constitutional crisis in jurisprudence establishes the point of departure. Using this notion in legal context opens a problem of adopting in this field more general and well-grounded perspectives on crises. Subsequently, I present the concept of crises in works of Edmund Husserl, Hannah Arendt, Reinhart Koselleck and Niklas Luhmann. Each of aforementioned sections is concluded with an explication of the concept of crises in perspective of adequate theory. My final task is to draw some most important consequences for understanding constitutional crisis, as well as the need for general theory of legal crises.